STUDI DESKRIPTIF KOMPETENSI PEDAGOGIK GURU SENI BUDAYA DI SMAN 3 KOTA PARIAMAN - Dedi Kurnia; Jagar Lumban Toruan; Tulus Handra Kadir (FBS Universitas Negeri Padang, 2017)
This research is to explain about Pedagogic Competence of Art and Culture Teacher in SMAN 3 Kota Pariaman. This type of research is qualitative with descriptive analytical approach. The location ofthis research is in SMAN 3 Kota Pariaman, in the even semester of the academic year 2017/2018. Technique of collecting research data is using instrument of interview and observation. Based on result of the research that has been done can be concluded that the pedagogic competence of art and culture teacher in SMAN 3 Pariaman City is classified as